2009
DOI: 10.1007/s10620-008-0685-0
|View full text |Cite
|
Sign up to set email alerts
|

Ileal Mucosal and Fecal Pancreatitis Associated Protein Levels Reflect Severity of Salmonella Infection in Rats

Abstract: PAP/RegIII protein is increased in enterocytes of the ileal mucosa during Salmonella infection and is associated with infection severity. PAP/RegIII is excreted in feces and might be used as a new and non-invasive infection marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…This indicated that it is the cleaved form of Reg3b that binds to the pathogens, not the full-length polypeptide. We have shown previously that the Reg3 protein is not precipitated even when centrifuged at 15,000 ϫ g (25). Therefore, the results presented here indicate that ileal mucosal Reg3b is able to directly bind both Salmonella and Listeria.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…This indicated that it is the cleaved form of Reg3b that binds to the pathogens, not the full-length polypeptide. We have shown previously that the Reg3 protein is not precipitated even when centrifuged at 15,000 ϫ g (25). Therefore, the results presented here indicate that ileal mucosal Reg3b is able to directly bind both Salmonella and Listeria.…”
Section: Resultssupporting
confidence: 58%
“…Reg3g and Reg3b expression was determined in the ileum because this is the area where expression is upregulated during infection of rats (22,25) and upon microbial colonization of germ-free mice (3). Frozen mucosal scrapings of the ileum were pulverized under liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reg III family genes are likely to act predominantly in the lower GI tract, and, therefore, we cannot support confidently the involvement of Reg I gene in NSAID-induced lower GI lesions. However, because REG family proteins are secreted into the GI tract lumen (26,27), it may be interesting to speculate that REG I protein produced in the upper GI tract may act in the lower GI tract as well.…”
Section: Discussionmentioning
confidence: 99%